Microwave dielectric and reflection analysis on pure and adulterated Trigona Honey and Honey Gold - Cheng, Ee Meng; Lee, Kim Yee; Khor, Shing Fhan; Mohd Nasir, Nashrul Fazli; Mohamad, Che Wan Sharifah Robiah; Abdul Aziz, Nor Azah; Mohd Tarmizi, Emma Ziezie; Baharuddin, Siti Aishah (Czech Technical University, 2022)
Honey adulteration is common in food industry, as it provides cheaper alternative for user to consume honey. However, it has been abused by industry runners with unsavory practices. It leads to business fraudulency. Pure honey is very precious due to its powerful health-giving properties. It rises attention of beekeeper, wholesaler, food manufacturer, retailer and consumer because this issue has been sensationally reported in media mass. Enforcement of law is initiated to mitigate the abuse and fraudulency. Apart from that, it motivates scientists, technologists and engineers to strive for an effective solution. Microwave sensing method is well known in agricultural product and food. Hence, dielectric and reflection response is explored for the potential of development of instrumentation system in gauging edible honeys. In this work, the dielectric and reflection measurement were conducted using Agilent E8362B PNA Network Analyzer in conjunction with Agilent 85070E Performance Probe from 0.5 GHz to 4.5 GHz. Dielectric and reflection measurement were conducted to investigate its dielectric behavior and mismatch impedance due to water and sucrose content in honey. It can be noticed that dielectric constant, ε’ decreases when frequency increases. In the meantime, ε’ decreases with increment of water and sucrose content for Honey Gold and Trigona Honey. Meanwhile, for water adulterated Honey Gold and Trigona Honey, loss factor, ε” decrease when frequencies increases. In addition, ε” decreases when water content < 36% and < 43% for Honey Gold and Trigona Honey, respectively. It can be found that at 1 GHz to 4 GHz, ε” increases when sucrose content increases which applicable for Honey Gold and Trigona Honey. In reflection measurement, magnitude of reflection coefficient, |Γ| decrease when frequency increases for all percentage of water and sucrose content for both honeys. Withal, phase, -φ increases as frequency increases for both water adulterated honeys. -φ varies insignificantly when sucrose content increases for both sucrose adulterated honeys.